Philosophy: Key Themes - Baggini, J. author. aut Link
IX, 210 p.
Keywords: Philosophy: Key Themes is a beginner's guide to understanding and critiquing philosophical arguments. Each chapter introduces one of the major themes in philosophy. Baggini's approach combines explanation with summary while encouraging the reader to question the arguments and positions presented.